Estimation of Length- Weight Relationship in Larva and Adult of Chrysomela populi (Coleoptera: Chrysomelidae) Obtained from Two Species of Salix - Singh, Amar Paul; Chandra, Agni; De, Kritish; Uniyal, Virendra Prasad (Indian Forester, 2022)
We have studied the relationship of length and weight of three larval stages and adults of leaf beetle Chrysomela populi taken from two species of Willow plants Salix alba and Salix fragilis at Lahaul, Himachal Pradesh, India. By performing Welch's t-test, we had found that there was no significant (p > 0.05) difference in the length and weight of the larvae and adults feed on two species of willow. For three larval stages and adults of C. populi feeds on S. alba andÂ  S. fragilis the relationship between the body weight and the length was explained by the linear regression equation very well (for all linear models R2 > 0.81, p < 0.05). This study will be helpful for effective management of pests of willow plant, particularly at Indian Trans Himalayan region.